2017
DOI: 10.1002/2017jd026872
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Modulate Properties of Primary Marine Aerosol Generated From Ambient Seawater on Ships at Sea

Abstract: Model primary marine aerosol (mPMA) was produced by bubbling clean air through flowing natural seawater in a high‐capacity generator deployed on ships in the eastern North Pacific and western North Atlantic Oceans. Physicochemical properties of seawater and mPMA were quantified to characterize factors that modulated production. Differences in surfactant organic matter (OM) and associated properties including surface tension sustained plumes with smaller bubble sizes, slower rise velocities, larger void fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
63
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(77 citation statements)
references
References 109 publications
(212 reference statements)
13
63
1
Order By: Relevance
“…This result is consistent with a number of laboratory studies which show an increase in coarse-mode aerosol production with increasing water temperature (e.g., Woolf et al, 1987;Mårtensson et al, 2003;Sellegri et al, 2006;Salter et al, 2014a). Indeed, there appears to be a number of physical and biological effects that can strongly perturb the bubbleaerosol production relationship (Keene et al, 2017). Extensive in situ measurement of aerosol particles within the marine atmospheric boundary layer is unlikely to be viable.…”
Section: User Requirements For Marine Aerosol Particle Emissionssupporting
confidence: 87%
“…This result is consistent with a number of laboratory studies which show an increase in coarse-mode aerosol production with increasing water temperature (e.g., Woolf et al, 1987;Mårtensson et al, 2003;Sellegri et al, 2006;Salter et al, 2014a). Indeed, there appears to be a number of physical and biological effects that can strongly perturb the bubbleaerosol production relationship (Keene et al, 2017). Extensive in situ measurement of aerosol particles within the marine atmospheric boundary layer is unlikely to be viable.…”
Section: User Requirements For Marine Aerosol Particle Emissionssupporting
confidence: 87%
“…mPMA production was previously characterized at the same hydrographic stations on Georges Bank (S‐1) and in the Sargasso Sea north of Bermuda (S‐3) as part of the Western Atlantic Climate Study (WACS) in August 2012 (Keene et al, ; Long, Keene, Kieber, et al, ; Table S2). During WACS, mPMA were emitted via the detrainment of bubble plumes produced in a high‐capacity generator similar in design and operation to that deployed in this study but configured with coarse (145 to 174 μm pore size) and fine (10 to 20 μm pore size) porosity sintered glass frits (Keene et al, ; Long, Keene, Kieber, et al, ) rather than forced‐air Venturis. Evaluation of results for the two campaigns, although not directly comparable, nonetheless yielded insights regarding influences of bubble plume properties on mPMA production.…”
Section: Methodsmentioning
confidence: 99%
“…The authors speculate that these differences are driven primarily by corresponding differences in size distributions of subsurface bubbles produced by these methods. However, a subsequent study reported minimal differences in number size distributions of mPMA produced from natural seawater by the detrainment of bubble plumes at similar air entrainment rates and mean depths but with significantly different bubble size distributions (Keene et al, ). The latter results suggest that the size distributions of subsurface bubbles may be less important in modulating the normalized size distributions of PMA than suggested in previous reports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most models, however, use simple source functions formulated in terms of wind speed only; the most widely used is that of Monahan et al (1986), which is often applied well beyond the range of conditions from which it was derived and for which it is valid (Spada et al,645 2013). Indeed, there appears to be a number of physical and biological effects that can strongly perturb the bubble/aerosol production relationship (Keene et al, 2017).…”
Section: User Requirements For Emissions: Marine Aerosol Particlesmentioning
confidence: 99%